HUBUNGAN TERAPI KOMPRES HANGAT DAN PEMBERIAN MINUMAN KUNYIT ASAM TERHADAP PENURUNUNAN NYERI DISMENORE PADA REMAJA PUTRI SMK SWAKARYA PALEMBANG - Yan Permadi; Siti Ramasida (STIKES Abdurrahman. Pusat Informasi dan Manajemen, 2020)
Menstruation is priodic and cyclic bleeding from the uterus, accompanied by releasing (escalation) of the endometrium. Basically menstruation is a process of catabolism and occurs under the influence of pituitary and ovarian hormones. Data obtained from the study conducted at Swakarya Palembang in 2019, the number of female students who experienced dysmenorrhea pain were 32 respondents. The purpose of this study was to determine the correlation of warm compress therapy and consumption of tamarind- turmeric drinks to reduce dysmenorrhea pain in female students. This study used a